Pain pressure thresholds and psychosocial correlates in people with knee osteoarthritis - Tew, Victoria Jane (2014)
This thesis focusses on chronic pain, pain sensitivity, depression, and anxiety in people with knee osteoarthritis (OA). The thesis includes details of three interrelated sub-studies: Study 1: An investigation into the associations between pain pressure thresholds (PPTs) and self-reported pain, depression, anxiety, and gender in knee OA; Study 2: An investigation into the inter-rater reliability of pressure algometry Quantitative Sensory Testing (QST); and Study 3: Rasch analysis of the State-Trait Anxiety Inventory short form (STAI-SF).